2020
DOI: 10.3390/brainsci10060406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Age, Acoustic Exposure, and Electrical Stimulation on Binaural Sensitivity in Adult Bilateral Cochlear Implant Patients

Abstract: Deafness in both ears is highly disruptive to communication in everyday listening situations. Many individuals with profound deafness receive bilateral cochlear implants (CIs) to gain access to spatial cues used in localization and speech understanding in noise. However, the benefit of bilateral CIs, in particular sensitivity to interaural time and level differences (ITD and ILDs), varies among patients. We measured binaural sensitivity in 46 adult bilateral CI patients to explore the relationship between bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 81 publications
(147 reference statements)
0
24
0
Order By: Relevance
“…Together these factors capture information relevant to a listener’s early and later auditory deprivation and experience. For additional details, please see [ 4 ]. To determine which factors to include in regression models associated with the different measures of performance, we used the step function in the lmerTest package for mixed-effects models and stats package for fixed-effects models in R. This performs stepwise model comparison to determine the model with the smallest Akaike information criterion (i.e., a measure of predictive power similar to adjusted R 2 in regression), removing factors that provide the least prediction and balancing the number of parameters with the increased model fit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these factors capture information relevant to a listener’s early and later auditory deprivation and experience. For additional details, please see [ 4 ]. To determine which factors to include in regression models associated with the different measures of performance, we used the step function in the lmerTest package for mixed-effects models and stats package for fixed-effects models in R. This performs stepwise model comparison to determine the model with the smallest Akaike information criterion (i.e., a measure of predictive power similar to adjusted R 2 in regression), removing factors that provide the least prediction and balancing the number of parameters with the increased model fit.…”
Section: Methodsmentioning
confidence: 99%
“…There is extensive literature documenting the impact of patient-dependent factors on localization error for listeners with BiCIs. Several factors associated with auditory deprivation and experience with BiCIs are predictive of sensitivity to cues used for localization, outlined by Thakkar and colleagues [ 4 ]. Age at onset of deafness [ 5 11 ], the duration of experience with unilateral or bilateral, acoustic or CI stimulation [ 5 , 6 , 8 , 10 , 12 14 ], and age at testing [ 15 17 ] are predictive of localization performance in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, perceptual factors play a role in the low contribution of ITDs in electric hearing. Even when ITDs are presented under the most favorable conditions (i.e., via the pulse timing and at a single interaurally place-matched electrode pair, directly stimulated via a research interface using the most sensitive pulse rate), CI listeners’ ITD sensitivity is lower and much more variable across listeners compared to that of NH listeners (Laback et al 2007 ; Majdak et al 2006 ; van Hoesel 2007 ; Thakkar et al 2020 ). Several explanations have been proposed for this perceptual deficit in electric hearing (see Laback et al 2015 , for a review).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, deprivation of binaural experience due to long periods before or between implantation on both ears results in cortical anomalies (Gordon et al 2010 ) as well as degraded neural ITD coding (Chung et al 2019 ; Hancock et al 2010 ). Accordingly, Thakkar et al ( 2020 ) reported that ITD sensitivity is related to the duration of bilateral hearing impairment and to CI experience. Another factor may be a mismatch between stimulation rate and membrane and synaptic parameters of binaural cells, which may explain the decline in sensitivity with increasing rate (Chung et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Improving binaural hearing has become highly relevant in clinical settings due to the appreciation of deaf patients’ needs to communicate and function in realistic, complex auditory environments. The study by Thakkar and colleagues [ 6 ] aimed to unrevealed how age-related, acoustic, and electric experience impact binaural sensitivity in adults with bilateral cochlear implants. Individuals with unilateral cochlear implant have difficulty with pitch perception, and adding a hearing aid in the non-implanted ear is potentially beneficial.…”
mentioning
confidence: 99%